#TITLE_ALTERNATIVE# - RACHMATULLAH (NIM 28100207), UDJI
In the development process, failures on project implementation are something happens many times. Its caused by the descend of technique design quality, for example we might see sometime physical substance of a project had damaged before its technique period ended. An impact of the failure itself is financial squanders. One of the technique design quality descend is caused by the chosen consultant which works not professionally. The low of work standard quality itself was causing by the consultant selection had done without maximum plan. In the other side, technique design, which made by plan consultant, is a quality assumption of a whole project implementation. As a technology development, normative changes, and needs and desire changes; the process of provision for a technique design consultant also needs to be appropriate to those changes. Especially, in order to go along to the technology changes, which needs adjustment on manpower skill and also method application.